Roman Diet and Meat Consumption: Reassessing Elite Access to Meat in 1 Corinthians 8 and 10. (December 2019) - Tite, Philip L.
A persistent exegetical tradition exists linking the Pauline controversy over the consumption of idol meat in the Corinthian correspondence to social and economic assumptions about the Roman world. Specifically, there is the assumption that access to meat was limited to the elite within the Roman world. According to this exegetical tradition, the lower classes only had access to meat through public religious festivals or as derivative through cultic sacrifice by means of the marketplace, resulting in the view that non-elites were sustained on a diet of legumes, grains and wine. Roman access to meat along such class demarcations, furthermore, is founded upon an economic dichotomy of elite and non-elite. This article challenges these social assumptions regarding meat consumption in, especially, Corinth by engaging recent scholarship that re-evaluates Roman diet in regard to access to meat and other animal products. Specifically, methods in archaeological science (especially stable isotope analysis) are used to supplement literary reassessments. What arises is a new picture of Roman diet, wherein meat consumption was not limited to the elite, but was prevalent in nearly all levels of Roman society. With this fresh perspective on Roman dietary practices, Paul's comments in 1 Corinthians 8 and 10 must be re-evaluated.